Coastline Change Surround Sekampung River Estuary Estimated by Geographic Information System Technique - Fahri, .; Syam, Tamaluddin (JOURNAL OF TROPICAL SOILS, 2011)
Surround a big river estuary coastline has a dynamic characteristic and change along a period of time, because of anatural process and/or it is accelerated by human activities. The surround Sekampung river estuary coastline located in Rawa Sragi area is one of the most dynamic coastlines in southern Lampung Province that has changed significantly from 1959 (as a natural process) to year 1987 (as an accelerated process by human activities) since the government of Indonesia has applied swamp drainage system for Rawa Sragi area. It is likely that the coastline has changed significantly in the period of 1987 to 2009 (as an increasing intensity of the human activities in the surrounding Rawa Sragi land). The objective of this research was to analyze the coastline change in the surrounding of Sekampung river estuary in two periods of time: (1) the change of the 1959 – 1987 period coastlines; and (2) the change of the 1987 – 2009 period coastlines. The method of this research was a GIS technique, the implementation was divided into three main steps: (1) the first analysis was conducted in laboratory include raster data source analysis and registration, coastline digitations, and overlaying and analysis of the coastline data; (2) field observation (ground check) was conducted to observe and verify the ground existing coastline; and (3) the last analysis wasconducted after ground check activity to improve and to verify the first coastline analysis results. The result of this research indicated that coastline change in the period of 1959 to 1987 increased the coast land as much as 717.19 hectares, but decreased the coast land as much as 308.51 hectares. Furthermore the coastline change in the period of 1987 to 2009 increased the coast land as much as 162.504 hectares, but decreased the coast land as much as 492.734 hectares. The 1959 – 1987 coastline change was a coast land increasing period, but the 1987 – 2009 coastline change was a coast land decreasing period.Keywords: Abrasion, accretion, coast land, coastline, estuary